Efisiensi Usaha Tani Padi Melalui Pengembangan SUTPA (Forum Penelitian Agro Ekonomi, 2016)
The objective of the assessment on Rice Based Agribusiness Oriented Farming System (Sutpa) conducted in rainy season (MB) 1995/96 is to find an agribusiness development model that is capable to increase fanning efficiency and commodity's competitive advantage. The Sutpa assessment implementation main characteristics are: (1) to introduce new engineered technology packeges to enhance productivity and production efficiency; (2) to applicate technology with an economic scale; (3) to implement tight field supervision by interdicsipline team consisting of research and extension workers; (4) to applicate participatory approaches in encouraging involved farmers to play their active roles; and (5) to enhance coordination with related official and local key persons to maintain the implementation harmony beginning from its planning, implementation and evaluation. In 1995/96, Sutpa assessment implementation was concentrated in 14 provinces with an area of 46.000 Ha (92 assessment plot unit), and in the following two years it was widened in 18 and 19 provinces. Some assessment results show that rice farming using direct seeding system developed in Sutpa assessment could reduce labor utilization for 17.01 - 38.56 percent and it was able to increase production and farmer's profit for 40.26 - 43.74 percent and 14.12 - 24.10 percent respectively compared to tilt of transplanting system. The competitive advantage analysis also shows that rice fanning direct seeding system gives a competitive profit compared to that of transplanting system's at 70.23 - 82.14 percent of the existing production level. The Sutpa assessment implementation has been able to escalate new high yielding varieties and direct seeding system adoptions.